2023
DOI: 10.3390/s23042081
|View full text |Cite
|
Sign up to set email alerts
|

Covert Channel Communication as an Emerging Security Threat in 2.5D/3D Integrated Systems

Abstract: In this paper, first, a broad overview of existing covert channel communication-based security attacks is provided. Such covert channels establish a communication link between two entities that are not authorized to share data. The secret data is encoded into different forms of signals, such as delay, temperature, or hard drive location. These signals and information are then decoded by the receiver to retrieve the secret data, thereby mitigating some of the existing security measures. The important steps of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Miketic et al [1] indicated that host-based, network-based, and physical are the three basic categories into which covert channels fall. The timing and storage characteristics of the host system are usually altered in host-based covert channels.…”
Section: Type Of Covert Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Miketic et al [1] indicated that host-based, network-based, and physical are the three basic categories into which covert channels fall. The timing and storage characteristics of the host system are usually altered in host-based covert channels.…”
Section: Type Of Covert Channelsmentioning
confidence: 99%
“…Wendzel et al [16] divide network covert storage channels into two categories: (i) techniques that change header fields or other non-payload elements and (ii) techniques Covert channel types [1].…”
Section: Network Covert Channel Classificationmentioning
confidence: 99%
See 1 more Smart Citation